Unlocking the Mental Space Image Through Cognitive Stylistics: Delineating the Namibian Autobiographical Texts - Lazarus Gawazah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study evaluates Namhila’s autobiography through cognitive stylistics theory, also known as the mental image space theory. It further sought to test whether the link, path and balance schemata were present and how they have been used in the autobiography. The schema theory in linguistics examines how “general” knowledge is needed to make sense of written texts. The study found out that the balance, link and path schemata are all present in Namhila’s autobiography. The schemata assist readers to better understand the autobiography with a balance as mental and physical equilibrium, links to relationships and path as journeys from the beginning to the end. The study recommends the application of other theories of stylistics to the analysis of the different genres of literary texts.